FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PADA PEKERJA GROUND HANDLING DI PT.X - Saputra, Adi; Dewi, Meri Kartika (ARCHIVE OF COMMUNITY HEALTH, 2024)
Job stress is a disorder that arises due to the gap between task demands and the capacity possessed by workers. The aviation industry is an industry that has a high risk of work stress, especially for ground handling workers. Work stress on ground handling workers can be influenced by two factors, namely individual and occupational factors. The purpose of this study was to determine the factors associated with work stress on ground handling workers at PT.X. This study uses primary data sources obtained from filling out questionnaires by respondents and the results of noise measurements. The research design used was a cross sectional study with a sample of 70 ground handling workers. Data analysis was performed univariately and bivariately using the chi-square test. The results of the analysis show that there are as many as 45 (64.3%) ground handling workers who experience work stress, and factors related to work stress on ground handling workers at PT.X, namely individual factors include age (p = 0.000), and years of service (p = 0.001), as well as work factors which include physical workload (p = 0.012), mental workload (p = 0.018), adherence to the use of APT (p = 0.013) and work shifts (p = 0.007). Therefore, workers are expected to be more obedient in using ear protection devices, managing workload and rest time, and doing activities that can be entertaining as an effort to prevent work stress management. Keywords: Work Stress, Individual Factors, Work Factors, Ground Handling